The role of uncertainty in the euro crisis: A reconsideration of liquidity preference theory - Toralf Pusch (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2012)
An active role of fiscal policy has been rediscovered as a crisis remedy at the beginning of the financial crisis all over Europe. More recently, the Euro Crisis with its mounting governments' funding costs for a number of Southern EU member states and Ireland has called this strategy into question. As opposed to this view, the main point of this contribution is to elaborate a link between rising sovereign risk premia in the Eurozone and a major feature of the financial crisis - which culminated in elevated uncertainty after the Lehman collapse. Theoretically, this link is developed with a reference to Keynes' liquidity preference theory. Empirically, a high explanatory power of rising uncertainty in financial markets and detrimental effects of fiscal austerity for the evolution of sovereign risk spreads are demonstrated by means of panel regressions and supplementary correlation analyses.
Keywords: E12; E62; G12; 330; Liquiditätspräferenz; Finanzmarktkrise; Finanzpolitik; Öffentliche Schulden; Länderrisiko; Finanzmarkt; Risikoprämie; Austeritätspolitik; Eurozone